2008
DOI: 10.1212/01.wnl.0000312278.40250.6e
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization state-dependent elevations of adiponectin in chronic daily headache

Abstract: Serum adiponectin levels are increased in women chronic daily headache (CDH) sufferers. In addition, visceral obesity, as measured by waist-to-hip ratio, is a risk factor for CDH in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 38 publications
3
85
1
3
Order By: Relevance
“…The required number of participants was inferred by results of studies analyzing adipokines in painful conditions, such as rheumatoid arthritis (16) and headache (17). We concluded that 25 patients would be required in each group to detect a 20% difference in adipokines and cytokines levels.…”
Section: Discussionmentioning
confidence: 99%
“…The required number of participants was inferred by results of studies analyzing adipokines in painful conditions, such as rheumatoid arthritis (16) and headache (17). We concluded that 25 patients would be required in each group to detect a 20% difference in adipokines and cytokines levels.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure is divided into three domains: the N-terminal domain, which has large variation in amino acids between species, the collagen-like domain, and the globular domain of the C-terminal region. 10 The secretion of adiponectin is strictly controlled by the retention of protein thiols, so that two molecular endoplasmic reticulum chaperones play a critical role: 44 kDa ER proteins (endoplasmic reticulum protein 44, ERp44) and Ero1-La (endoplasmic reticulum oxidoreductin 1-like alpha), both induced during adipogenesis. ERp44 forms a disulfide bond with adiponectin, which is important for the maturation of trimeric and hexameric proteins of high-, medium-and low-molecular weight in oligomers.…”
Section: Structure and Secretion Of Adiponectinmentioning
confidence: 99%
“…However, adiponectin can exert either pro-or anti-inflammatory properties depending on the form and multimer of adiponectin involved that varies in molecular weights (high (HMW), middle (MMW), or low (LMW) molecular weight) and forms. In a study episodic migraineurs showed a similar trend toward higher levels of total and high molecular weight adiponectin though neither measure reached statistical significance [61]. HMW: LMW ratio of adiponectin was suggested to be potential novel biomarkers for episodic migraine and either antagonist of high molecular weight adiponectin or agonists of low molecular weight adiponectin, or both suggested to be potential targets for headache management.…”
Section: Inflammation-mediated Link Between Obesity and Migrainementioning
confidence: 94%
“…In contrast, LMW adiponectin can inhibit endotoxin-mediated release of IL-6. Adiponectin bears a remarkable similarity to leukocyte activating agent IL-2 and regulates both innate and adaptive immune responses and generally increases levels of pro-inflammatory cytokines and activation of monocytes via the production of cytokines such as TNFα and IL-6 and can induce the expression of nitric oxide and prostaglandin in cultured macrophages [52,[59][60][61][62][63].…”
Section: Inflammation-mediated Link Between Obesity and Migrainementioning
confidence: 99%